TERRITORIAL CONTEXT OF HUNGARIAN SMART AND AUTONOMOUS VILLAGES - Némediné Kollár, Kitti (Studia Mundi – Economica, 2022)
This manuscript aims to review the key concepts of smart villages, autonomous villages and alternative energy sources and to present their key spatial context. Nowadays, the role of SMART factors in the economy of settlements is important (present of digitalisation) and the definition of smart villages, smart solutions, alternative energy sources and eco-settlements and autonomous villages in the countryside. Closely related to all this the SMART Rural21 flagship project. In this manuscript we are focusing on the relationship between smart systems and sustainability in rural areas. We are looking for the answer to the following question: How can make easier the digitalisation and the presence of alternative energy sources daily life of rural settlements?